Preventative Effect of Zingiber officinale on Insulin Resistance in a High‐Fat High‐Carbohydrate Diet‐Fed Rat Model and its Mechanism of Action. (15th February 2014) - Li, Yiming; Tran, Van H.; Kota, Bhavani P.; Nammi, Srinivas; Duke, Colin C.; Roufogalis, Basil D.
Abstract Insulin resistance is a core component of metabolic syndrome and usually precedes the development of type 2 diabetes mellitus. We have examined the preventative effect of an ethanol extract of ginger (Zingiber officinale, Zingiberaceae) on insulin resistance in a high‐fat high‐carbohydrate (HFHC) diet‐fed rat model of metabolic syndrome. The HFHC control rats displayed severe insulin resistance, whilst rats treated with ginger extract (200 mg/kg) during HFHC diet feeding showed a significant improvement of insulin sensitivity using the homeostatic model assessment of insulin resistance (HOMA‐IR) after 10 weeks (p < 0.01). An in vitro mechanistic study showed that (S)‐[6]‐gingerol, the major pungent phenolic principle in ginger, dose‐dependently (from 50 to 150 μM) increased AMPK α‐subunit phosphorylation in L6 skeletal muscle cells. This was accompanied by a time‐dependent marked increment of PGC‐1α mRNA expression and mitochondrial content in L6 skeletal muscle cells. These results suggest that the protection from HFHC diet‐induced insulin resistance by ginger is likely associated with the increased capacity of energy metabolism by its major active component (S)‐[6]‐gingerol.